Forest Environment Supports for Community-Based Tourism Development - ERNAWATI, Ni Made; VODA, Mihai; SUDHANA, IGP Fajar Pranadi; SUDARMIN, Ni Made (Journal of Environmental Management and Tourism, 2019)
This article explores sustainable approaches of using forests for tourism. This article is developed base on an exploratory study reflected on using forest as recreational area in the Indonesian context particularly in Bali. This study was conducted by reviewing activity reports, articles on ecotourism, and regulations especially in Indonesia. It discusses the current practices and the existing regulations related to the issues and presents recommendations for a safer way of using forest for tourism. It is discovered that: in anticipation to the high demand of forest tourism currently, tourism activities in forests especially the protected forests need to be regulated, guidelines need to be developed, e.g. the basic structures required incorporate sustainable designed and use environmentally friendly materials. Promoting local communities to manage forest tourism is for community development and this could become a solution to the prolonged conflict between locals and forest authorities. It is expected that the result could foster sustainable practices within forest tourism and in a broader spectrum of ecotourism specifically in Bali and in Indonesia in general; promote the use of the natural environment to support the living of people around the area without damaging the ecosystem.